Analysis of the technical level of developments in the field of mobile charging installations for electric transport - A. R. Safin; V. R. Basenko; M. F. Nizamiev; A. N. Tsvetkov; T. I. Petrov (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE. The lack of easily accessible charging stations is becoming a negative factor in the growth of the adoption of electric vehicles. Consequently, the planning and placement of charging stations is gaining momentum among researchers around the world. One of the promising solutions is the use of mobile charging stations, which can solve the problem of the stationarity of existing solutions. TARGET. To confirm the relevance of the study and determine the current technical level in the field of charging stations for electric vehicles (for comparison with the technology being developed on the basis of Kazan State Power Engineering University and the Zarnitsa production association), an analysis of patent information was made. METHODS. The authors of the article defined terms and keywords for analysis, collected data on specialized sites and carried out a detailed analysis of a number of patents from different countries, research organizations. RESULTS. The maximum level of development is at the level of TRL 3-5, but the analysis of patent activity indicates an increase in the number of intellectual property objects, which may indicate a future sharp increase in the level of TRL, and the need for their own developments ready for mass production, for which the authors developed a flowchart of the developed mobile electric vehicle charging installation, indicating the features: the ability to supply power to the network, wireless charging for electric vehicles, the availability of all major types of charging for electric vehicles, the possibility of integrating renewable energy sources, dynamic energy distribution. CONCLUSION. The technical level of developments in the field of mobile charging stations for electric vehicles does not allow talking about ready-made solutions that can be used to develop the charging infrastructure of the Russian Federation, and the development of a domestic solution in the form of mass production is necessary.